2014
DOI: 10.5194/hess-18-2305-2014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uncertain precipitation data on insurance loss estimates using a flood catastrophe model

Abstract: Abstract. Catastrophe risk models used by the insurance industry are likely subject to significant uncertainty, but due to their proprietary nature and strict licensing conditions they are not available for experimentation. In addition, even if such experiments were conducted, these would not be repeatable by other researchers because commercial confidentiality issues prevent the details of proprietary catastrophe model structures from being described in public domain documents. However, such experimentation i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 71 publications
(78 reference statements)
5
37
0
Order By: Relevance
“…To our knowledge, so far only Sampson et al (2014) have analysed the effects of different precipitation scenarios on flood losses in depth. However, the Sampson et al study focused on an urban area and on a (relatively) small scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, so far only Sampson et al (2014) have analysed the effects of different precipitation scenarios on flood losses in depth. However, the Sampson et al study focused on an urban area and on a (relatively) small scale.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the input data, the choice of the impact indicators, the scale, and the vulnerability models are relevant sources of uncertainty (Ward et al, 2013;Apel et al, 2008;Merz and Thieken, 2009;de Moel and Aerts, 2011). In particular, vulnerability functions are considered as one of the most relevant sources of uncertainty in flood loss estimation (Ward et al, 2013;Sampson et al, 2014). Thus, uncertainty analysis is a key aspect in flood risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent advances in reduced-10 complexity flood models (Bates et al, 2010;Coulthard et al, 2013a) with simplified physics have shown promise in estimating flood depths, extent and velocity in urban areas (Fewtrell et al, 2011;Ramirez et al, 2016;Sampson et al, 2014). These models are particularly suited for data sparse locations, with large spatial extents (> 500 km 2 ), and urban topography represented by fine spatial resolution (≤ 30 m) digital elevation models (DEMs).…”
mentioning
confidence: 99%
“…Dankers et al (2007) used an RCM to evaluate the benefits of using high spatial resolution climate information for the Danube basin. Sampson et al (2014) have also demonstrated the importance of the resolution of precipitation data for a region of Ireland for hydrological impact modelling.…”
Section: Mathison Et Al: South Asia River-flow Projections and Thmentioning
confidence: 99%
“…These factors are all important given the limited computational resources available. The GCMs are the following: the third version of the Met Office Hadley Centre Climate Model (HadCM3; Pope et al, 2000;Gordon et al, 2000, a version of the Met Office Unified Model) and ECHAM5 (third realization; Roeckner et al, 2003) are downscaled using the HadRM3 RCM . These two GCMs capture the uncertainty in the sign of the projected change in precipitation with one showing an increase (HadCM3) and the other a decrease (ECHAM5).…”
Section: Gcm and Rcm Forcingmentioning
confidence: 99%